Being vertical: staging the vertical subject on the Manchester Salford border. Issue 5 (19th October 2020) - Brake, Jane; van Aitken, John
Abstract : Brake and Aitken present artistic work, photography and speculative poetics, which explore the emerging sensorium of the vertical city and its tentative subjects. With reference to the case study of Anaconda Cut, Salford UK, the article considers the development of the housing commodity through its participation in aesthetic capitalism and the role of atmospheres and design in the staging of vertical lifestyles. The research considers photographs and other marketing materials related to Anaconda Cut as they evidence the deployment of atmospheres and the production of affective sensory spaces, highlighting the way renting an apartment is framed within contemporary notions of positional and hedonistic consumption.